2017
DOI: 10.1111/1756-185x.13120
|View full text |Cite
|
Sign up to set email alerts
|

Comparing polyarteritis nodosa in children and adults: a single center study

Abstract: To our knowledge, this is the first study comparing characteristics of adult and childhood onset PAN. Our results have suggested that juvenile PAN had a more benign course (with less renal and neurologic involvement, shorter duration of induction treatment) than adult onset PAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…That is, there are no laboratory ndings that can be used to de nitely diagnose either childhood-or adult-onset PAN. Evidence suggests that childhood-onset PAN affects girls more than boys, in contrast to adult-onset PAN [8,20,21]. Although we enrolled only a small number of patients, the prevalence of PAN appeared slightly higher in boys (n = 6) than in girls (n = 3).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…That is, there are no laboratory ndings that can be used to de nitely diagnose either childhood-or adult-onset PAN. Evidence suggests that childhood-onset PAN affects girls more than boys, in contrast to adult-onset PAN [8,20,21]. Although we enrolled only a small number of patients, the prevalence of PAN appeared slightly higher in boys (n = 6) than in girls (n = 3).…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies [6,12,20] have reported that skin involvement and arthralgia/arthritis are more common in children than in adults with PAN. In contrast, weight loss and renal, gastrointestinal, and neurologic involvement appear to be more common in adults with PAN.…”
Section: Discussionmentioning
confidence: 96%
“…In children, relapse rate varied widely from 8.9%, up to 75% in the French series with the longest follow‐up . The observed mortality appeared somewhat lower in children, with mortality rates of 0–9.5% in pediatric series, versus 13.9–24.7% in adult series …”
Section: Classical Panmentioning
confidence: 93%
“…It is a systemic, necrotizing medium‐sized vessel vasculitis. It mainly affects adults, but pediatric series have also been published . Classification for both adult and childhood onset PAN have been developed, and the clinical features often overlap with DADA2 (Table ) …”
Section: Classical Panmentioning
confidence: 99%
See 1 more Smart Citation